March : a novel - Brooks, Geraldine (Penguin Books, 2006)
An extraordinary novel woven out of the lore of American history by the author of the international bestseller Year of Wonders. From Louisa May Alcott's beloved classic Little Women, Geraldine Brooks has animated the character of the absent father, March, and crafted a story "filled with the ache of love and marriage and with the power of war upon the mind and heart of one unforgettable man" (Sue Monk Kidd). With"pitch-perfect writing" (USA Today), Brooks follows March as he leaves behind his family to aid the Union cause in the Civil War. His experiences will utterly change his marriage and challenge his most ardently held beliefs. A lushly written, wholly original tale steeped in the details of another time, March secures Geraldine Brooks s place as a renowned author of historical fiction